Development of a pulsation dampener for hydraulic systems of power plants - A. N. Kryuchkov; M. A. Еrmilov; E. N. Еrmilova; I. V. Balakhonov; A. N. Vidyaskina (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2019)
The article considers the development of a capacitance-type pressure pulsation dampener. The pressure pulsation dampener is used to reduce the noise of hydraulic systems which are subject to increased requirements for vibro-acoustic characteristics. The developed pressure pulsation dampener is a flexible element with negligible hydraulic resistance. This element contains a gas cavity the pressure in which depends on its deformation. Overall dimensions of the dampener under investigation do not exceed the dimensions of a standard pipeline. This property, along with its low hydraulic resistance, is an advantage over its analogues. The article analyzes the known pressure pulsation dampeners and considers two design schemes of the proposed device. The experimental results of analyzing the dampener that showed its high efficiency (5 ... 40 dB) in a wide range of pressure oscillations in the fluid flow (20 ... 3000 Hz) are presented.